KNOWLEDGE, SKILLS, AND WORK STYLES OF EXECUTIVE SECRETARY AS PERCEIVED BY THE INDUSTRIES - Lenda Mambo (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
The present level of technological advancement in 4.0 business and industry revolution has required the professional secretaries to adapt their knowledge/skills/work style in line with these technological explosions in records creation/management/processing/storage as well as the record maintenance and retrieval. The objective of the study is to find out the industry requirements of the secretarial profession in order to align them with the curriculum and classroom training of the secretarial students. The 39 criteria of 4.0 industrial revolution characteristics of “knowledge, skills, and work-styles attitude” in form of a questionnaire was distributed to 38 samples of executives. Quantitative as well as qualitative methods and descriptive analysis were used to analyze the data. The result shows that the most important aspect of an office secretarial competency is attitude (M=4.50; SD=0.77), followed by skill (M=4.44; SD=0.83), knowledge (M=4.14; SD=0.90). The study recommends that the development of secretarial professional education must be based on correctly handle the relationship between theoretical classroom teaching, practical office training with the emphasizes on systematically incorporate the 4.0 professional attitude with the skills and knowledge as proposed by industries